On the issue of a mandatory forensic comprehensive psychological and psychiatric examination of capacity: pro arguments - Kantor, P. (Psihologiâ i pravo, 2016)
The article again addresses the issue of forensic examinations of incapacity or limited capacity due to the mental disorder in the Code of Civil Procedure of the Russian Federation. The article critically discusses the common objections to establishing a mandatory appointment for a comprehensive forensic psychological and psychiatric examination in this category of cases. The author observes how this proposed requirement is connected with earlier legislation updates. The new rule logically follows from the need to consider, in according to law, a person’s ability for decision making and social communication. Currently, a comprehensive forensic psychological and psychiatric examination is appointed too rarely in these cases, which leads to the insufficient comprehension of these significant factors by the courts. Organizational and technical hurdles, which are considered to be main arguments against the discussed rule, shouldn’t prevent the long overdue legislation innovations. Statistical data presented by the opponents relates to different categories of cases and, therefore, cannot be a basis for the conclusions about the issue discussed. Статья обращается к вопросу о процедуре назначения судебной экспертизы в Гражданском процессуальном кодексе Российской Федерации при рассмотрении гражданских дел о лишении либо ограничении дееспособности вследствие психического расстройства. В статье критически разбираются возражения против введения нормы об обязательной комплексной психолого-психиатрической экспертизе по этой категории дел. Указывается на взаимосвязь такой нормы с предшествующими изменениями законодательства. Изменение в порядке назначения экспертизы логически вытекает из потребности учитывать в соответствии с законом способности гражданина к принятию решений и социальному взаимодействию. В настоящее время комплексная психолого-психиатрическая экспертиза по этой категории дел назначается слишком редко, что приводит к тому, что существенные для дела обстоятельства остаются невыясненными судами. Организационно-технические препятствия, которые выдвигаются в качестве основных доводов против обсуждаемой нормы, сами по себе не могут блокировать назревшие изменения законодательства. Приводимые оппонентами статистические данные относятся к другим категориям дел и не могут служить основанием для выводов по обсуждаемой проблеме.